Sea change - White, Karen (Karen S.) (New York New American Library, 2012)
A lonely woman with a life-long feeling of not quite belonging elopes with a child psychologist she met at a conference and discovers how difficult it is to actually escape her past.
Php 750.00
Donated by Gorriceta-Rojo family 12.11.18
Keywords: Family secrets -- Fiction